Trajectory tracking for a mobile robot with skid-slip compensation in the vector-field-orientation control system - Michałek, Maciej; Dutkiewicz, Piotr; Kiełczewski, Marcin; Pazderski, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
The article is devoted to a motion control problem for a differentially driven mobile robot in the task of trajectory tracking in the presence of skid-slip effects. The kinematic control concept presented in the paper is the Vector Field Orientation (VFO) feedback approach with a nonlinear feed-forward skid-slip influence compensation scheme. The VFO control law guarantees asymptotic convergence of the position tracking error to zero in spite of the disturbing influence of skid-slip phenomena.
Keywords: differentially driven mobile robot; skid-slip compensation; trajectory tracking; vector fields